Online Recurrent Me-thod Of Credibilistic Fuzzy Clusterin - Bodyanskiy, Ye. V.; Shafronenko, A. Yu.; Rudenko, D. A.; Klymova, I. N. (My University, 2020)
An online method of reliable fuzzy clustering is proposed, designed to analyze data sequentially received for processing. A feature of the developed approach is the use of the membership function of a special kind described by the density function of the Cauchy distribution. The actual procedure for clarifying the centroids of clusters is essentially a self-learning rule “The Winner Takes More” (WTM), in which the neighborhood function is generated by the introduced membership function.
Keywords: Fuzzy clustering; processing; gradient optimization; membership level; online mode